Identifying Predictors of Mortality in Sepsis Patients with Malignancy: A Retrospective Cohort Study - Leonard Nainggolan; Rido Prama Eled; Ikhwan Rinaldi; Cleopas Martin Rumende; Chyntia Olivia Maurine Jasirwan; Suryo Anggoro Kusumo Wibowo; Robert Sinto; Khie Chen Lie (Interna Publishing, 2024)
Background: Sepsis is a major problem that contributes to a high mortality rate. Its mortality is especially high in patients with malignancy. One study reported that sepsis patients with malignancy have a 2.32 times higher risk of mortality compared to patients without malignancy. For this reason, factors that influence mortality in sepsis patients with malignancy become especially important to provide effective and efficient therapy. This study aims to identify factors that influence mortality in sepsis patients with malignancy. Methods: This study is a retrospective cohort study using medical records of sepsis patients with malignancy who were treated at Cipto Mangunkusumo Hospital from 2020 to 2022. A bivariate analysis was carried out and followed by a logistic regression analysis on variables with p-value<0.25 on the bivariate analysis. Results: Among the 350 eligible sepsis subjects with malignancy, there was an 82% mortality rate (287 subjects). Bivariate and multivariate analyses revealed significant associations between mortality and both SOFA score (adjusted Odds Ratio of 5.833, 95%CI 3.214-10.587) and ECOG performance status (adjusted Odds Ratio of 3.490, 95%CI 1.690-7.208). Conclusion: SOFA score and ECOG performance status are significantly associated with sepsis patient mortality in malignancy cases.